Transcranial Magnetic Stimulation of Human Adult Stem Cells in the Mammalian Brain - Kremer, Karlea L.; Smith, Ashleigh E.; Sandeman, Lauren; Inglis, Joshua M.; Ridding, Michael C.; Koblar, Simon A. (Frontiers in Neural Circuits, 2016)
Introduction: The burden of stroke on the community is growing, and therefore, so is the need for a therapy to overcome the disability following stroke. Cellular-based therapies are being actively investigated at a pre-clinical and clinical level. Studies have reported the beneficial effects of exogenous stem cell implantation, however, these benefits are also associated with limited survival of implanted stem cells. This exploratory study investigated the use of transcranial magnetic stimulation (TMS) as a complementary therapy to increase stem cell survival following implantation of human dental pulp stem cells (DPSC) in the rodent cortex. Methods: Sprague-Dawley rats were anaesthetised and injected with 6x105 DPSC or control media via an intracranial injection, and then received real TMS (TMS0.2Hz) or sham TMS (TMSsham) every 2nd day beginning on day 3 post DPSC injection for 2 weeks. Brain sections were analysed for the survival, migration and differentiation characteristics of the implanted cells. Results: In animals treated with DPSC and TMS0.2Hz there were significantly less implanted DPSC and those that survived remained in the original cerebral hemisphere compared to animals that received TMSsham. The surviving implanted DPSC in TMS0.2Hz were also found to express the apoptotic marker Caspase-3. Conclusions: We suggest that TMS at this intensity may cause an increase in glutamate levels, which promotes an unfavourable environment for stem cell implantation, proliferation and differentiation. It should be noted that only one paradigm of TMS was tested as this was conducted as an exploratory study, and further TMS paradigms should be investigated in the future.